48=96p

Simple and best practice solution for 48=96p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 48=96p equation:


Simplifying
48 = 96p

Solving
48 = 96p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-96p' to each side of the equation.
48 + -96p = 96p + -96p

Combine like terms: 96p + -96p = 0
48 + -96p = 0

Add '-48' to each side of the equation.
48 + -48 + -96p = 0 + -48

Combine like terms: 48 + -48 = 0
0 + -96p = 0 + -48
-96p = 0 + -48

Combine like terms: 0 + -48 = -48
-96p = -48

Divide each side by '-96'.
p = 0.5

Simplifying
p = 0.5

See similar equations:

| -5(-4)-4y=20 | | 8-5/7=-32 | | 15-7y=-42 | | 3(x-1)-2x=-2+3(x-1) | | -21=2a-7 | | -3=12y-5(2y-7)18 | | -5(-5)-4y=20 | | 7+2n=-1 | | 18x=1/3 | | 0.4t=16 | | 36x^2+24x-7=0 | | ((-8y^3/4)/(y^3z^6))^-1/3 | | 36x^2+24-7=0 | | 8-3p=3(-p-2)-7(3p-6) | | -25x+51-47x=225 | | 5x+3.2=18.2 | | 21x-(3x-9)=18 | | 4x-2x+5=0 | | 105=2x-5(2x-13) | | 72-16=x | | -3x=14y | | 6-4a=2(-a+3)-4(2a-1) | | 6x-(-4x+2)=(x-1)-5(7x-8) | | 46x-2(3x-15)=60 | | [p-5]-12=-9 | | 3(-t+3)-5(4t-1)=t+2+3t | | y=2/3x-1 | | x(x+3)=4 | | x/2-1/x=(6x+5)/12 | | (x-5)(x-5)=25 | | 5x=-3x+21 | | 19/6+4y=8y-1/6 |

Equations solver categories